A Study on Roadside Noise Generated by Tricycles. - Vergel, Karl N. (Philippine engineering journal.)
The study is aimed at quantifying the levels of noise contributed by tricycles in the roadside residential environment. Specific objectives include the measurement of roadside noise levels, relating noise levels and road traffic flow characteristics and relating the noise performance of tricycles with loading, speed and road gradient (sloping or level) at on-road conditions, and with type of engine, loading, fuel-oil mix ratio and type of lubricant at simulated loading conditions. Tricycles comprise majority of the traffic passing through the study area. Results from the 24-hour survey of noise levels have shown that all readings exceeded the existing local standards. A multiple linear regression model predicting roadside noise level as a function of the traffic speed and tricycle traffic volume is developed with a relatively high correlation, indicating the significant contribution to noise by tricycles. There is a relationship of on-road noise performance of tricycles with its speed and load and type of road. With respect to noise performance under simulated loading, there is an increase in noise level with increase in speed level.